2010
DOI: 10.1002/bsl.940
|View full text |Cite
|
Sign up to set email alerts
|

Risk communication of terrorist acts, natural disasters, and criminal violence: Comparing the processes of understanding and responding

Abstract: Risk communication is an important vehicle for the scientific understanding of the perception of and response to various kinds of threats. The present study provides apparently the first empirical attempt to compare perceptions, decision-making, and anticipated action in response to threats of three kinds: natural disaster, violent crime, and terrorism. A total of 258 college undergraduates were surveyed using a vignette-based, 2 × 2 × 3 between-subjects design that systematically manipulated threat imminence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 55 publications
2
19
0
1
Order By: Relevance
“…Evidence from a hypothetical scenario study showed that participants appraised different types of disasters (crime, natural disaster, terrorist attack) as similar in risk, but they differed in the intentions to take protective actions. For example, in a natural disaster scenario participants were more likely to state they would change their daily activities than in a crime scenario (Heilbrun et al 2010). The cognitive appraisal of a given situation as dangerous may influence the readiness to engage and the choice of protective actions.…”
Section: What Is Rp? Defining Rp During Fire Evacuationmentioning
confidence: 99%
“…Evidence from a hypothetical scenario study showed that participants appraised different types of disasters (crime, natural disaster, terrorist attack) as similar in risk, but they differed in the intentions to take protective actions. For example, in a natural disaster scenario participants were more likely to state they would change their daily activities than in a crime scenario (Heilbrun et al 2010). The cognitive appraisal of a given situation as dangerous may influence the readiness to engage and the choice of protective actions.…”
Section: What Is Rp? Defining Rp During Fire Evacuationmentioning
confidence: 99%
“…This work has been extended to communicating the risks of climate change, perceptions of which are influenced by individual differences in scientific knowledge, the ability to understand numeric information, and sociopolitical group identification (e.g., Hart, ; Kahan et al ., ). Natural disaster risk communication also has a well‐developed literature, although there is little yet known about how best to communicate the risk of case‐specific events (e.g., Heilbrun, Wolbransky, Shah, & Kelly, ) which would be relevant to offender‐specific risk communication. Heilbrun et al .…”
Section: Lessons Learned From Non‐forensic Risk Communicationmentioning
confidence: 99%
“…Heilbrun et al . () directly compared responses to the communication of risks concerning natural disasters, terrorism, and violent offending, and concluded that the salience and potency of natural disaster risks were qualitatively different from the other scenarios. In the remainder of this section, therefore, we focus on lessons learned from medical risk communication, including attempts to influence patient decision‐making.…”
Section: Lessons Learned From Non‐forensic Risk Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from a hypothetical scenario study showed that participants appraised different types of disasters (crime, natural disaster, terrorist attack) as similar in risk, but they differed in the intentions to take protective actions. For example, in a natural disaster scenario participants were 10 more likely to state they would change their daily activities than in a crime scenario [72]. The cognitive appraisal of a given situation as dangerous may influence evacuation motivation.…”
Section: Transactional Stress Modelmentioning
confidence: 99%